Pengelolaan Program Kesehatan Masyarakat Melalui Forum Kesehatan Kelurahan Siaga - Rahayu, Dian; Nurdin , Ambia; Khairuman; Lestari, Diana (Teewan Journal Solutions, 2024)
This article discusses the role and management of public health programs through the Siaga Village Health Forum (FKKS) as an innovation in efforts to improve community well-being. FKKS is a participatory platform that involves various stakeholders, including the government, healthcare professionals, and the local community, to design, implement, and monitor health programs at the village level. This research explores the implementation of FKKS in addressing various challenges in community health at the local level. Through qualitative methods and case studies, the authors analyze the successes and obstacles faced by FKKS in improving access to health services, enhancing community health literacy, and building resilience capacity in facing disasters and health emergencies. This article provides policy recommendations to strengthen the role of FKKS as an inclusive and sustainable strategy for managing community health programs. With a deep understanding of the factors influencing the success of FKKS, it is hoped that this will provide guidance for policymakers, healthcare practitioners, and communities to optimize community health programs at the village level.